GAMBARAN PENILAIAN KLINIS UNTUK SINDROM FRAGILE X PADA PENYANDANG RETARDASI MENTAL - Eny Waeningsih,*Siti Aminah,* Paulus Anam Ong* (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION FRAGILE X SYNDROME FXS IS THE COMMONEST FORM OF XLINKED INHERITED MENTAL RETARDATION FXS PATIENTS SHOW CHARACTERISTIC ABNORMALITIES SUCH AS LONG AND NARROW FACE PROMINENT EARS TESTICULAR ENLARGEMENT COGNITIVE IMPAIRMENT HYPERACTIVITY AND AUTISTIC BEHAVIOR